Carbon dioxide capture efficiency using algae biological absorbent and solid adsorbent for biogas purification - Adinurania, Praptiningsih Gamawati; Setyobud, Roy Hendroko; Wahono, Satriyo Krido; Mel, Maizirwan; Nindita, Anggi; Purbajanti, Endang; Harsono, Soni Sisbudi; Malala, Andoniana Rakoto; -, Salafudin; Sasmito, Andi (Universiti Teknologi Malaysia, 2016)
CO2 is the main gas impurity on biogas production which must be reduced to produce optimum CH4 content of biomethane. This biogas purification research was conducted at experiment field of PT Bumimas Ekapersada, Cikarang, Bekasi, Jawa Barat, Indonesia from April until June 2013. The research purpose was compare the purification results of four sorption materials: (i) imported products of solid adsorbent; (ii) domestic products of solid adsorbent; (iii) biological absorbent of Scenedesmus sp., and (iv) wild algae which grow on cat fish (Clarias gariepinus) pond as biological liquid absorbent. This research was repeated six times to produce average (in percentage) of CO2 capture efficiency and used t test as statistical inference. Solid adsorbent test utilized a cylinder measured (diameter × length) 10 cm × 50 cm, filled with 2.3 kg to 2.5 kg adsorbent materials. Liquid absorbent test utilized a cylinder measured (diameter × length) 10 cm × 100 cm. The test results showed that there were no significant statistical different among the sorption materials. Therefore, imported products of solid adsorbent can be replaced by domestic products and solid adsorbent can be replaced also by biological absorbent of Scenedesmus sp. and/ or wild algae absorbent.